Transfer Pricing In The Balkans - (:unkn) unknown (My University, 2017)
This study aims to show the recent developments and differences in the transfer pricing applications of several Balkan states. Transfer pricing applications in Bulgaria, Greece, Romania, Albania, Macedonia, Serbia and Turkey are examined respectively according to OECD Transfer Pricing Guidelines. OECD is considered as the highest authority in transfer pricing practices but findings indicate that some Balkan states’ transfer pricing legislations do not integrate with OECD’s transfer pricing policies. Therefore, EU’s Code of Conduct for TP Documentation for Associated Enterprises and local legislations of the mentioned Balkan states are additionally analyzed in the research.

Bu çalışma Balkan ülkelerindeki transfer fiyatlaması uygulamalarındaki gelişmeleri ve farklılıkları incelemektedir. Transfer fiyatlaması konusunda OECD’nin transfer fiyatlaması yönetmelikleri belirleyici bir rol oynamaktadır. Bu nedenle, Bulgaristan, Yunanistan, Romanya, Makedonya, Arnavutluk, Sırbistan ve Türkiye’deki transfer fiyatlaması uygulamaları OECD’nin transfer fiyatlaması yönetmeliklerine uygun olarak karşılaştırılmıştır. Balkan ülkeleri arasında transfer fiyatlaması konusunda bir birliktelik olmadığı, transfer fiyatlaması yönetmeliklerinin bazılarının OECD’nin yönetmelikleri ile uyumlu olmadığı çalışmanın bulguları arasındadır.
Balkanlarda Transfer Fiyatlaması
Keywords: İktisat; Tarih; İşletme